Synthesis and anticancer activity of new [(Indolyl)pyrazolyl]-1, 3, 4-oxadiazole thioglycosides and acyclic nucleoside analogs. (3rd July 2017) - El-Sayed, Wael A.; El-Sofany, Walaa I.; Hussein, Hoda A. R.; Fathy, Nahed M.
ABSTRACT: New [(Indolyl)pyrazolyl]-1, 3, 4-oxadiazole compounds and their derived thioglycosides as well as the corresponding sugar hydrazones were synthesized. The acyclo C -nucleoside analogs of the oxadiazoline base system were also prepared by reaction of acid hydrazides with aldehydo sugars followed by one pot process encompassing acetylation and cyclization of the synthesized hydrazones. The anticancer activity of the newly synthesized compounds was studied against colorectal carcinoma (HCT116), breast adenocarcinoma (MCF7) and prostate cancer (PC3) human tumor cell lines and a number of compounds showed moderate to high activities.